Objective sleep measures after endoscopic sinus surgery in patients with chronic rhinosinusitis. Issue 7 (23rd November 2020) - Little, Ryan E.; Alt, Jeremiah A.; Ramakrishnan, Vijay R.; Platt, Michael P.; Schlosser, Rodney J.; Storck, Kristina A.; Soler, Zachary M.
Abstract : Background: Poor sleep quality is common in chronic rhinosinusitis (CRS). Prior studies have demonstrated improvements in patient‐reported measures of sleep quality following endoscopic sinus surgery (ESS). The purpose of this study was to evaluate the effect of ESS on objective sleep parameters and identify any associations between specific objective measures and patient characteristics, comorbidities, and patient‐reported outcome measures (PROMs). Methods: Adults with CRS undergoing ESS were prospectively enrolled from 4 centers across North America. Any subject previously diagnosed with a known primary sleep disorder was excluded. Objective sleep indices were recorded using a portable sleep diagnostic device preoperatively and postoperatively. Patient‐reported outcome instruments were completed including the Pittsburgh Sleep Quality Index (PSQI) and the 22‐item Sino‐Nasal Outcome Test (SNOT‐22). Results: Thirty‐six patients (mean age 47 years, 56% male) completed baseline and postoperative sleep studies with mean ± standard deviation (SD) follow‐up 9.6 ± 7.7 months. Mean PSQI and SNOT‐22 before and after ESS was 10.2 ± 3.9 vs 7.8 ± 4.4 ( p = 0.001); and 54.6 ± 14.6 vs 28.5 ± 15.3 ( p < 0.001), respectively. Total sleep time, sleep latency, and awakenings after sleep onset did not change following ESS (all p > 0.5) despite improvements in PSQI and SNOT‐22. Changes in PSQI did not correlate with comorbidities or objective sleep indices (all p > 0.1). Conclusion: In this multicenter prospective cohort, objective sleep indices were not improved following ESS for CRS despite significant improvements in patient‐reported sleep quality and CRS‐specific QOL.